Detection and functional resolution of soluble immune complexes by an FcγR reporter cell panel - Haizhang Chen; Andrea Maul‐Pavicic; Martin Holzer; Magdalena Huber; Ulrich Salzer; Nina Chevalier; Reinhard E Voll; Hartmut Hengel; Philipp Kolb (EMBO Molecular Medicine)
Abstract Fc‐gamma receptor (FcγR) activation by soluble IgG immune complexes (sICs) represents a major mechanism of inflammation in certain autoimmune diseases such as systemic lupus erythematosus (SLE). A robust and scalable test system allowing for the detection and quantification of sIC bioactivity is missing. We developed a comprehensive reporter cell panel detecting activation of FcγRs. The reporter cell lines were integrated into an assay that enables the quantification of sIC reactivity via ELISA or a faster detection using flow cytometry. This identified FcγRIIA(H) and FcγRIIIA as the most sIC‐sensitive FcγRs in our test system. Reaching a detection limit in the very low nanomolar range, the assay proved also to be sensitive to sIC stoichiometry and size reproducing for the first time a complete Heidelberger‐Kendall curve in terms of immune receptor activation. Analyzing sera from SLE patients and mouse models of lupus and arthritis proved that sIC‐dependent FcγR activation has predictive capabilities regarding severity of SLE disease. The assay provides a sensitive and scalable tool to evaluate the size, amount, and bioactivity of sICs in all settings.